Cost and Outcomes Analysis of Polypoidal Choroidal Vasculopathy (Aneurysmal Type 1 Neovascularization) Treatment Strategies. (May 2021) - Feng, Paula W.; Lin, James; Sakurada, Yoichi; Yannuzzi, Nicolas A.; Smiddy, William E.; Chilakamarri, Priyanka; Mehta, Nitish; Modi, Yasha S.; Parikh, Ravi
Purpose: This work compares the relative cost utility of ranibizumab and aflibercept with and without verteporfin photodynamic therapy (vPDT) for the treatment of polypoidal choroidal vasculopathy. Methods: A retrospective cost and outcomes analysis of the PLANET (Efficacy and Safety of Intravitreal Aflibercept for Polypoidal Choroidal Vasculopathy) and EVEREST II (Efficacy and Safety of Ranibizumab With or Without Verteporfin Photodynamic Therapy for Polypoidal Choroidal Vasculopathy) studies was performed. Clinical utilization and outcomes were based on data from these clinical trials, and costs were obtained from Medicare fee schedules. Cost utility was derived from published visual outcomes and expressed as quality-adjusted life-years (QALYs). Cost per QALY and cost per line of vision gained for each treatment strategy (in US dollars) were assessed as the main outcome measure. Results: The 1-year facility (nonfacility) costs per QALY were 295, 744.41 (260, 088.19), 209, 574.09 (182, 831.77), 211, 072.63 (188, 425.33), and 212, 275.22 (189, 703.05) for ranibizumab as-needed monotherapy, ranibizumab as-needed with combination therapy, aflibercept monotherapy, and aflibercept with delayed vPDT combination therapy, respectively. Conclusions: Ranibizumab as-needed monotherapy was the least clinically effective and least cost efficient over 1 year. Ranibizumab as-needed with combination therapy, aflibercept monotherapy, and aflibercept with deferred vPDT combination therapy all had similar overall cost utility at 1 year. If bevacizumab were to be substituted for ranibizumab, the cost per QALY could be reduced by approximately a factor of 5, showing the benefit of bevacizumab for increasing the cost utility of polypoidal choroidal vasculopathy treatment.